Produksi Organ Bicara Bahasa Arab - Raodhatul Jannah (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
The field of linguistics that studies, analyzes, and discusses the sequences of language sounds is called phonology. The sound units that are the object of the study are phonetic and phonemic. In the case of issuing, producing, or uttering sounds, of course through the process. Human speech organs consist of the respiratory system, esophagus and oral cavity, nose and throat which then work together to produce a sound, both in the form of consonants and Arabic vowels. The consonant study in this case relates to the characteristics, pronunciation of articulation and the place where the sound is released.